Lifestyle mobilities : intersections of travel, leisure and migration / Edited by Tara Duncan; Scott A Cohen; Maria Thulemark - Cohen, Scott A Edited
Being mobile in today's world is influenced by many aspects including transnational ties, increased ease of access to transport, growing accessibility to technology, knowledge and information and changing socio-cultural outlooks and values. These factors can all engender a (re)formation of our everyday life and moving - as and for lifestyle - has, in many ways, become both easier and much more complex. This book highlights the crossroads between concepts of lifestyle and the growing body of work on 'mobilities'. The study of lifestyle offers a lens through which to study the kinds of moorings